Pengaruh Penambahan Packing Pada Performa Tray Column: Studi Simulasi Cfd - Haykal, Muhammad Husin; Taufany, Fadlilatul; Altway , Ali (Publikasi Indonesia, 2025)
This study conducted a Computational Fluid Dynamics (CFD) simulation to analyze the hydrodynamics and mass transfer in a distillation column, focusing on the impact of adding steel wool packing on a sieve tray. Tray columns are commonly used in distillation processes but have drawbacks such as low separation efficiency and high pressure drop due to uneven flow distribution. As a solution, modifying the column by adding packing above the sieve tray has been proven to enhance mass transfer and tray efficiency. The study employed a multiphase Eulerian model, the k-epsilon turbulence model, and the species transport model to simulate a binary ethanol-water system. The simulation results show that the addition of steel wool packing produces smaller and more uniform bubbles, thereby increasing the interfacial area and the contact time between vapor and liquid. This leads to a more structured gas flow and a higher ethanol vapor concentration at the tray outlet, indicating improved separation efficiency compared to using sieve trays alone. This research provides an in-depth understanding of the internal physical phenomena that support the performance enhancement of distillation columns through the addition of packing.